2020
DOI: 10.1016/j.chiabu.2019.104257
|View full text |Cite
|
Sign up to set email alerts
|

Crossing boundaries: A pilot study of maternal attitudes about child maltreatment in nine countries

Abstract: Background: Definitions of child maltreatment vary widely between studies, and even more so between different cultural contexts. Objective: In this pilot study, we examine between-country variations in maternal notions about what constitutes child maltreatment. Participants and setting: The sample consisted of 466 mothers recruited in Chile,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This difference may be related to cultural differences in family rearing styles and people’s cognitive understanding of the concepts of abuse and neglect. Notably, in a study of mothers’ perceptions of child abuse and neglect in nine countries, Chinese mothers had significantly higher thresholds for marking behaviors as abuse (i.e., fewer behaviors were considered abusive) than mothers in all other countries ( Mesman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be related to cultural differences in family rearing styles and people’s cognitive understanding of the concepts of abuse and neglect. Notably, in a study of mothers’ perceptions of child abuse and neglect in nine countries, Chinese mothers had significantly higher thresholds for marking behaviors as abuse (i.e., fewer behaviors were considered abusive) than mothers in all other countries ( Mesman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic constraints in certain regions of the world are known to contribute to neglectful behavior towards children by their caregivers (Mesman et al, 2020). In any culture it is harmful to neglect a child, but the parent's conception about what exactly is harmful for their children are typically rooted in their actions' need for an intervention.…”
Section: Neglect Cross Culturallymentioning
confidence: 99%
“…Chinese people generally regard physical punishment as a necessary parenting technique (Zhao et al, 2017). A multi-country comparison found that Chinese people have the highest threshold for labeling behaviors as maltreatment (Mesman et al, 2020). Such high tolerance for childhood violence may reduce child post-traumatic depression, as children might rationalize such violent behaviors.…”
Section: Ethnic Disparities In Maltreatment Traumamentioning
confidence: 99%